E-BOOK MINDFULNESS: MEDIA PANDUAN INTERAKTIF UNTUK MENINGKATKAN SELF-REGULATION PESERTA DIDIK - Arbain Fajar A. Hamid; Sahril Buchori; M. Amirullah (UIN Sunan Kalijaga Yogyakarta, 2026)
This research aims to develop a mindfulness e-book as an interactive self-regulation guidance medium for vocational high school (SMK) students. The research employed the Research and Development (R&D) method using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model adapted from Robert Maribe Branch. Analysis of needs was conducted with 49 students, comprising 4 validators (2 content experts and 2 media experts). The BRS (Brief Resilience Scale) was administered to one group (small group) and 30 students. Data collection utilized self-regulation and mindfulness questionnaires. The research findings indicate that students possessed low self-regulation skills, with awareness aspects lacking judgment, attention, and ability to self-regulate emotions. The design phase yielded an e-book in PDF format with portrait layout, utilizing a combination of blue and white colors. The development phase produced an e-book with a validity percentage of 97% based on expert judgment and 96% from student assessment, categorized as highly valid. The practical category attained 95% after expert judgment, categorized as highly practical. This research concludes that the mindful self-regulation e-book has been proven valid and practical as an interactive guidance medium for enhancing students' self-regulation through private counseling services. Keywords: e-book mindfulness, self-regulation, vocational high school students